The November 2015 Mw6.4 earthquake effects in Lefkas Island - D. Kazantzidou-Firtinidou; Kassaras, I.; S. Tonna; A. Ganas; E. Vintzileou; C. Chesi (ICONHIC - 1st International Conference on Natural Hazards & Infrastructure, 2016)
This work describes the outcome of two field surveys in Lefkada Island, after the 17.11.2015 earthquake of Mw6.4 at its southwestern peninsula. Geo-environmental effects were observed throughout the western flanks of the mountain massif, parallel to the activated fault. Structural damage was mainly observed in the epicentral area where macroseismic intensity was assessed as VIII, based on registered damage and assumed vulnerability per building typology. Both modern and traditional buildings exhibited notable seismic performance. The distribution of the damage per building category present in the affected area is presented, based on site surveys and post-seismic usability characterization by the local Earthquake Rehabilitation Organization. The survey highlights the frequent presence of the so-called “pontelo” dual system at both ground floor and two-story stone masonry buildings at the western mountain villages. This structural type, unique within the Greek territory, revealed significant seismic performance and the need of engineering restoration measures is underlined.